Cadmium exposure is associated with chronic kidney disease in a superfund site lead smelter community in Dallas, Texas - Bert B. Little; Giang T. Vu; Brad Walsh (Taylor & Francis Group, 2023)
Background: The study was conducted in a Dallas lead smelter community following an Environmental Protection Agency (EPA) Superfund Cleanup project. Lead smelters operated in the Dallas community since the mid-1930s.Aim: To test the hypothesis that cadmium (Cd) exposure is associated with chronic kidney disease (CKD) ≥ stage 3.Subjects and methods: Subjects were African American residents aged ≥19 to ≤ 89 years (n=835). CKD ≥ stage 3 was predicted by blood Cd concentration with covariates.Results: In logistic regression analysis, CKD ≥ stage 3 was predicted by age ≥ 50 years (OR = 4.41, p < 0.0001), Cd level (OR = 1.89, p < .05), hypertension (OR = 3.15, p < 0.03), decades living in the community (OR = 1.34, p < 0.003) and T2DM (OR = 2.51, p < 0.01). Meta-analysis of 11 studies of Cd and CKD ≥ stage 3 yielded an ORRANDOM of 1.40 (p < 0.0001). Chronic environmental Cd exposure is associated with CKD ≥ stage 3 in a Dallas lead smelter community controlling covariates.Conclusion: Public health implications include screening for heavy metals including Cd, cleanup efforts to remove Cd from the environment and treating CKD with newer renal-sparing medications (e.g., SGLT-2 inhibitors, GLP-1s).